Omega‐3 polyunsaturated fatty acids and chronic stress‐induced modulations of glutamatergic neurotransmission in the hippocampus. (13th January 2014) - Hennebelle, Marie; Champeil‐Potokar, Gaëlle; Lavialle, Monique; Vancassel, Sylvie; Denis, Isabelle
<x xml:space="preserve">Abstract</x> Chronic stress causes the release of glucocorticoids, which greatly influence cerebral function, especially glutamatergic transmission. These stress‐induced changes in neurotransmission could be counteracted by increasing the dietary intake of omega‐3 polyunsaturated fatty acids (n‐3 PUFAs). Numerous studies have described the capacity of n‐3 PUFAs to help protect glutamatergic neurotransmission from damage induced by stress and glucocorticoids, possibly preventing the development of stress‐related disorders such as depression or anxiety. The hippocampus contains glucocorticoid receptors and is involved in learning and memory. This makes it particularly sensitive to stress, which alters certain aspects of hippocampal function. In this review, the various ways in which n‐3 PUFAs may prevent the harmful effects of chronic stress, particularly the alteration of glutamatergic synapses in the hippocampus, are summarized.